Characterisation of the second binding protein of immunoglobulin (SBi) in Straphylococcus aureus - Smith, Emma Jane (Trinity College (Dublin, Ireland). School of Genetics and Microbiology, 2011)
The second binding protein for immunoglobulin (Sbi) of Staphylococcus aureus comprises two IgG binding domains (D1 and D2) that share 30% sequence homology with the IgG binding domains of protein A (Spa) and two domains (D3 and D4) that bind to and trigger the consumption of complement factor C3. Sbi is assumed to be expressed on the cell surface but its C-terminal domain 'Y' lacks motifs found in proteins that are bound to the cell wall or membrane of Gram-positive bacteria.
Keywords: Genetics & Microbiology, Ph.D.; Ph.D. Trinity College Dublin.